BECKER, Christian U. Sustainability Ethics and Sustainability Research. - Antonio de Souza Lopes, Marcos; Antonio Picoli, Rogério (Revista Estudos Filosóficos - UFSJ, 2017)
BECKER, Christian U. Sustainability Ethics and Sustainability Research. New York: Springer. 2012. 139 p.